Features of Vespa affinis Nest Based on X-ray Diffraction, Spectroscopic, and Surface Morphological Studies - Salprima Yudha S; Octakireina Liesaini Daefisal; Swadexi Istiqphara; Anisa Ulya Darajat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The main focus of this research is to ascertain the X-ray diffraction (XRD) pattern, Fourier transform infrared (FTIR) spectroscopic pattern, and surface morphology of a hornet (Vespa affinis) nest. The optical microscopic(OM) analysis demonstrated that the nest presented an irregular formation of partition materials. This was confirmed via scanning electron microscopy (SEM), which revealed the presence of a unique form with a honeycomb-like pattern. Meanwhile, the materials largely consisted of carbon and oxygen elements, as was revealed by the energy dispersive X-ray (EDX) analysis, while the XRD analysis indicated that the nest was composed of amorphous materials of cellulose and lignin. Finally, the (FTIR) spectroscopy analysis revealed the presence of a number of peaks, which indicated that the material also consisted of a mixture of cellulose, hemicellulose, and lignin materials. It is envisaged that these results would widen the possibilities of fundamental scientific research on forest products, particularly the use of the V. affinis nest for further biological and chemical research.